Does early childbearing affect utilization of antenatal care services and infant birth weight: evidence from West and Central African region - Sagalova, Vera; Le Dain, Anne-Sophie; Bärnighausen, Till; Zagre, Noel Marie; Vollmer, Sebastian (Journal of global health, 2021)
Background Adequate antenatal care (ANC) utilization is recognized as one of the important drivers of safe childbirth and positive birth outcomes. The usage of ANC services fluctuates with various personal, socio-economic, and cultural characteristics and in resource-poor settings, adolescent mothers are at a particularly high risk of insufficient ANC utilization. Objectives This paper investigates whether the usage of ANC services and institutional delivery as well as newborn birth weight differ systematically between adolescent and adult mothers in West and Central Africa. Moreover, we explore to what extent differences in birth weight are explained by ANC usage, adolescence, and select socio-economic characteristics of the mother. Methods We pooled cross-sectional data from all Demographic and Health Surveys (DI IS) and Multi Indicator Cluster Surveys (MICS) conducted in countries in West and Central Africa region between 1986 and 2017 to estimate measures of ANC usage and qualified delivery assistance (along with a combined measure of "adequate maternal healthcare" aggregating these two factors) and newborn birth weight by maternal age group. We estimated various regression models to analyze a) the association between adolescence and adequate prenatal and maternal health care controlling for select socio-economic maternal characteristics as well as the local environment and b) between adolescence, adequate maternal health care, and newborn birth weight outcomes, also controlling for maternal characteristics and the local environment. All regressions were linear probability models for binary outcomes and simple linear models for continuous outcomes. Results Adequate maternal health care provision was lowest among adolescent mothers: 23.0% among adolescents vs an average of 29.2% across all other age groups. Moreover, we found maternal education and wealth to be positively and significantly associated with receiving adequate maternal health care. Adolescent mothers had the highest risk of low infantile birth weight with 14.5% (95% confidence interval (CI)=13.6%-15.5%), which is roughly 1.5-2 times higher than in older mothers. We found that adolescence is still strongly associated with low birth weight even when adequate maternal health care and various socio-economic factors as well as the local environment are controlled for. Conclusions Our findings suggest that ANC supply in resource-poor settings should be particularly tailored to adolescent mothers' needs and that further research is necessary to explore what individual maternal characteristics beyond socio-economic and physical (eg, BMI) factors drive the prevalence of low birth weight. Moreover, the currently used measures of maternal care quality are heavily dependent on pure quantitative measures (number of ANC visits). New indicators incorporating measures of factual quality and scope ought to be developed and incorporated into large routine household surveys such as DHS and MICS.